Implementasi Kebijakan Normalisasi Sungai Kalianak di Kota Surabaya dalam Mendukung Penataan Ruang Wilayah - Putri , Falindra Syahla; Radjikan; Muhammad Roisul Basyar (Public Administration Dept, Faculty of Social and Political Science, 2026)
The Kalianak River represents one of the most critical flood-prone areas in Surabaya due to severe narrowing, sedimentation, and reduced water capacity, which have repeatedly caused flooding events. The Surabaya City Government implemented a river normalization policy based on Regional Regulation No. 12 of 2014 concerning Spatial Planning (RTRW) for 2014–2034 as part of flood mitigation and spatial management efforts. This study aims to analyze the effectiveness of policy implementation using the Van Meter and Van Horn model, focusing on six implementation indicators. This research employs a qualitative descriptive approach. The data were collected through interviews, observations, and documentation. Informants in this study consisted of officials from the Surabaya City Government, particularly the Public Works Department (Dinas PU), local authorities, and community members living around the KalianaK River area. The findings indicate that the implementation of the river normalization policy has been relatively effective in terms of policy clarity, inter-agency coordination, and implementer commitment. However, several obstacles remain, including social resistance, economic limitations, and political pressures. Therefore, a stronger social approach, law enforcement, and community engagement are required to ensure the sustainability of the policy implementation.